PERANCANGAN KENDALI GARASI RUMAH BERBASIS WEB VIA WIRELESS LAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
In this research designed data communication system for home based garage control via wireless LAN. Data communication systems for Web-based control via the wireless LAN is a system used to monitor and control the garage door with the web remotely. Controlling center lies in a browser that can be accessed through a smartphone connected to a LAN network that will be the user interface with the garage door to be controlled. In this system will be paired Ethernet module connected wireless router as telecommunications media. With this system, the user can control the monitor, garage door remotely while it is connected to the wireless router. So the user does not need manual control at close range, the user can also know the state-controlled garage door via the web. The final stage is a software design then the system can be tested as a whole to determine the ability of the system, response time required to perform the command system. And QoS parameter this is a response time and throughput. Testing by means of ping test to obtain. After that will be analyzed in the response time and throughput it takes to send commands from a web browser that is controlled from a smartphone to a microcontroller. The results obtained after the system has been created is a system can connect to a local area network in a home and after testing all of obtained the required response time of the system to perform the command average time 48.106 ms and throughput/ transmission speed 10.989 bit/sec. It can be concluded that the design of microcontroller-based web browser via LAN wireless can be implemented.